Strategic managerial accounting hospitality, tourism and events applications - Jones, Tracy; Atkinson, Helen; Lorenz, Angela (Goodfellow Publishers, 2012)
This text explores the nature of these industry sectors and how these impact on the strategic managerial accounting (SMA) tools used by decision makers in the industry. Formerly known as Managerial Accounting in the Hospitality Industry by Harris and Hazzard, this new edition builds on this successful and well known text.